Comparison of Three Roche Hepatitis B Virus Viral Load Assay Formats - Pyne, Michael T. (American Society for Microbiology, 2012)
Two FDA-approved (in vitro diagnostic [IVD]) hepatitis B virus (HBV) viral load assays, the manual Cobas TaqMan HBV Test for use with the High Pure System (HP) and the automated Cobas AmpliPrep/Cobas TaqMan HBV Test v2.0 (CAP/CTM), were compared to a modified (not FDA-approved) version of the HP assay by automating the DNA extraction using the Total Nucleic Acid Isolation (TNAI) kit on the Cobas AmpliPrep. On average, CAP/CTM measurements were 0.08 log IU/ml higher than HP results (n = 206), and TNAI results were 0.17 log IU/ml higher than HP results (n = 166). The limit of detection (LOD), as determined by probit analysis using dilutions of the 2nd HBV international standard, was 10.2 IU/ml for CAP/CTM. The data sets for HP and TNAI were insufficient for probit analysis; however, there was 100% detection at ≥5 or ≥10 IU/ml for TNAI and HP, respectively. Linearity was demonstrated between 60 and 2,000,000 IU/ml, with slopes between 0.95 and 0.99 and R(2) values of >0.99 for all assays. Total precision (log percent coefficient of variance [CV]) was between 0.8% and 2.1% at 4.3 log IU/ml and between 1.4% and 4.9% at 2.3 log IU/ml. Correlation of samples, reproducibility, linearity, and LOD were acceptable and similar in all assays. The CAP/CTM assay and, to a lesser extent, the TNAI assay reduced hands-on time due to automation. There were no instances of contamination detected in negative samples during the course of the study, despite testing several samples up to 9.6 log IU/ml. The incidence of false-positive negative controls in HP and CAP/CTM clinical testing was <0.5% over 6 to 7 months of testing.